Guidelines for initial care of burn patients at the Maringá University Hospital (Research, Society and Development, 2023)
This study aimed to develop a flowchart for the initial care of adult burn patients at the University Hospital of Maringá. Method: To this end, an integrative literature review was conducted from 2012 to 2022, with a qualitative approach of full articles in English, Portuguese, and Spanish available in the SciELO (Scientific Electronic Library Online), PubMed/Medline (Online System for Search and Analysis of Medical Literature), LILACS (Latin American and Caribbean Literature on Health Sciences), CAPES Periodical Portal databases. As descriptors were used the terms: Guidelines (Guideline); Burns (Burn); Emergency (emergency); Burn Units (Burn Units).    As exclusion criteria: studies patients aged